Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.